A comparative study between cobrapla and laryngeal mask airway classic in spontaneous ventilating adult patients - Azmin Huda, Abdul Rahim (Universiti Sains Malaysia, 2007)
The purpose of this study is tp _assess whether the newly developed CobraPLA is a reliable, easy and safe device for use in adult patient undergoing general anaesthesia. We compared the use of the CobraPLA with the laryngeal mask airway in spontaneously ventilating adult patients undergoing general anaesthesia for elective surgery.· A randomized prospective study was conducted on 56 premedicated adult patients of ASA 1 and 2, aged between 18 to 65 years. They were divided into 2 groups ( n= 28/ group) receiving either CobraPLA or LMA as airway device. After inhalational induction of anaesthesia with intravenous propofol 2mglkg and intravenous fentanyl 1 meg/kg, the CobraPLA or LMA was inserted and the patients breathed spontaneously throughout the surgery. Anaesthesia was maintained with nitrous oxide, oxygen and sevoflurane. The airway device was removed at the end of surgery with the patients fully awake. The duration of insertion and number of attempts needed to successfully secure the airway wa~ recorded. Systolic blood pressure. diastolic blood pressure, mean arterial blood pressure , heart rate, saturation and end tidal carbon dioxide at different time interval were recorded. The incidence of post operative complications were also recorded. We found that there was longer time of insertion in the CobraPLA group as compared to LMA group and the difference was statistically significant. However there was no difference in the number of attempts needed to secure the respective airways. The ETC02 was higher in the CobraPLA group as compared to LMA group and the difference was statistically significant. Saturation was found to be higher in the LMA group and the difference was also statistically significant. However there was no difference in haemodynamic changes. Incidence of blood staining of the airway devices was higher in the CobraPLA group and was statistically significant. Nevertheless the incidence of sore throat was equal in both groups. We concluded that during spontaneous ventilation in adult patients undergoing general anaesthesia; the CobraPLA is not as reliable in providing a satisfactory airway and we consider it is not a suitable alternative to the_ laryngeal mask airway.